Morphological Analysis of Word Formation Found in VOA News Articles - Annisha Dyuli Adha; Rahma Dania (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This research was aimed to analyze the types word formation and their processes which found in English articles of VOA News. This research used descriptive qualitative approach. The method in collecting the data was by searching the data in VOA News related to the articles of education, health, and science and technology. The data that contained word formation were collected and classified them based on its categories, then analyzed them based on the processes of how the words are formed. The results of this research showed that there were six types of word formation found in the VOA News articles, they were derivation, compound, acronym, initialism, clipping/ abbreviation, and conversion. From those types, compound was the most common word formation found in the articles because it was the basic division in forming the words.